Performance evaluation of a three-stage composite wet scrubber for removing particulate matter. Issue 1 (December 2020) - Zhang, Bin; Hu, Chengming; He, Jinjie; Sui, Chunjie; Chen, Wei
Abstract: A three-stage composite wet scrubber was designed and developed to scrub fly ash particles through different modules from the effluent gas stream of an industrial production. The flue gas entering the scrubber is purified by the falling film scrubbing of Raschig ring packing, the spraying settlement of water mist, the mesh water film interception of grilles, and the electrostatic adsorption of filaments, thereby removing particulate matter and water mist. In the experiment, the particle removal efficiency at different packing heights, the inlet concentrations of fly ash and the inlet flow rates of flue gas were investigated. The experimental results show that, without any additives or pretreatment, the packing height is 30 cm, the particle removal efficiency of the new scrubber can reach more than 99.5%, and the outlet concentration is less than 8.75 mg/m 3 when the inlet concentration of fly ash is less than 12.53g/m 3 and the inlet flow rate is less than 12.13 m 3 /s. The three-stage composite wet scrubber was evaluated to add a novel scrubber in the list of wet scrubbers for industrial applications. This wet scrubber has a simple structure, easy operation, improved compactness, and high efficiency at low energy consumption.